Evaluation of the CD40 receptor-ligand system in the patients with atrial fibrillation of non-valvular genesis - O. N. Ogurkova; M. A. Dragunova; T. E. Suslova; Yu. G. Lugacheva; R. E. Batalov (Медицинская иммунология)
Thromboembolic syndrome is the most dangerous complication of atrial fibrillation which develops in about 8-15% of cases, thus presuming the role of persisting left-heart thrombosis in presence of anticoagulant therapy in some patients. When activated, the blood platelets express multiple copies of CD40L on their membrane. Hence, the soluble form of CD40 ligand is considered a marker of platelet activation and pathogenic processes associated with increased activity of the thrombotic system. Our aim was to study the content of CD40, soluble CD40 ligand and thrombomodulin in the patients with atrial fibrillation of non-valvular genesis receiving anticoagulant therapy, discerning those with a history of thrombotic complications, and the cases with atrial fibrillation, however, free of thrombotic complications. The study group included 22 healthy volunteers and 60 patients diagnosed with atrial fibrillation who received anticoagulant therapy, of whom 21 patients have developed thrombotic complications in the course of adequate anticoagulant therapy. Quantitative assays of CD40, soluble CD40 ligand and soluble thrombomodulin were performed by enzyme immunoassay using Core Facility “Medical Genomics”, Tomsk National Research Medical Center. Concentration of soluble CD40 ligand in both groups of the patients with atrial fibrillation significantly exceeded appropriate values in the group of healthy volunteers. CD40L content was increased in the group of patients with thrombotic complications against the group of patients without thrombotic complications. Thrombomodulin content in blood serum was decreased in the patients with thrombotic complications, as compared to both thrombosis-free patients, and to practically healthy volunteers. The study of CD40/CD40L system and thrombomodulin showed that the patients with thrombotic complications exhibited higher serum level of soluble CD40L, with a simultaneous decrease of thrombomodulin, a physiological anticoagulant. A comparative analysis of the CD40/sCD40L system showed increased concentrations of the biomarkers in females, when compared to males.